Educação financeira no ensino médio: um ensino com significado - Oliveira, José Roberto (2023)
This work, entitled "Financial education in high school: a meaningful teaching", linked to the Graduate Program in Science and Mathematics Teaching at the University of Passo Fundo (PPGECM/UPF), in the research line Information, Communication and Interaction Technologies applied to the teaching of Science and Mathematics, was developed together with a State Elementary and Secondary Education Network in the city of Porto Velho (RO), in a class of the second grade of high school. A didactic sequence was constructed based on David Ausubel's Theory of Meaningful Learning (TAS), which addressed financial mathematics in the understanding of the value of money over time, and was supported by the use of spreadsheet software. The general objective was to identify the implications of a didactic sequence, based on the Theory of Meaningful Learning, in the process of teaching Financial Education, with a class of second grade high school students. The research methodology used was qualitative, which permeates the entire process and not just the final result, valuing the participation of those involved, students and researchers. The teaching sequence was applied through expository dialogue classes, video classes, circle discussions, investigative instruments, questionnaires, diagnostic assessment, summative assessment and seminar. The discussions resulting from the data analysis are reported during each of the meetings. The results were positive, as the students demonstrated that they assimilated the content, mainly by producing financial budgets satisfactorily, and their defenses, in the seminar, relating topics of Financial Education to what was worked on during the teaching sequence. This showed that the cognitive structures of these students became more defined and expanded, inferring that there were signs of significant learning. Finally, the educational product that is part of this dissertation is available on the educational products portal of the Graduate Program in Science and Mathematics Teaching at the University of Passo Fundo.